A novel microbial fuel cell with exchangable membrane – application of additive manufacturing technology for device fabrication - Dawid Zawadzki; Paulina Pędziwiatr; Karina Michalska (ACTA INNOVATIONS, 2018)
Research about exploitation the potential of waste and sludge increased drastically in the recent years. One of the most promising alternative methods of waste management is Microbial Fuel Cell (MFC), which generate clean bio-electricity using microorganisms. Organic compounds, sewage, municipal solid waste could be used as a source for microbial nutrition. The construction of MFC is one of the most important parameter in laboratory studies and during scale-up. The efficiency of MFC depends on many factors including type of membrane. To obtain optimization in terms of various operating conditions, a prototype of Microbial Fuel Cell with exchangeable membrane was projected and fabricated by additive manufacturing (AM) technology. This novel device allows to research effects of different types of separator membranes. Preliminary research showed possibility to produce 3D printed MFC systems.